Biopsy and re-biopsy in lung cancer: the oncologist requests and the role of endobronchial ultrasounds transbronchial needle aspiration - Tuzi, Alessandro; Bolzacchini, Elena; Suter, Matteo B.; Giaquinto, Alice; Passaro, Antonio; Gobba, Stefania; Vallini, Ilaria; Pinotti, Graziella (Journal of Thoracic Disease, 2017)
As the leading cause of death worldwide, lung cancer has proven itself incurable in the advanced stages. For early stages, endobronchial ultrasounds transbronchial needle aspiration (EBUS-TBNA) is now considered the standard to assess mediastinal lymph node, to define the multimodality therapeutic approach. In recent years, EBUS-TBNA has extended its use also in the metastatic and locally recurrent disease. New molecules, with specific mutations that give resistance to current target therapies, have made re-biopsy at disease progression an important assessment, with therapeutic and clinical implication. Here we present the oncologist’s point of view on EBUS-TBNA in the staging process, at recurrence and progression.